Feasible tuning of barrier energy in PEDOT:PSS/Bi2Te3 nanowires-based thermoelectric nanocomposite thin films through polar solvent vapor annealing. (January 2020) - Kim, Wan Sik; Anoop, Gopinathan; Jeong, Il-Seok; Lee, Hye Jeong; Kim, Hyun Bin; Kim, Soo Hyeon; Goo, Gi Won; Lee, Hyunmyung; Lee, Hyeon Jun; Kim, Chingu; Lee, Joo-Hyoung; Mun, Bongjin Simon; et al.
Abstract: For next-generation energy harvesting thermoelectric (TE) devices based on organic/inorganic composites, the barrier energy at interfaces of components is critical in determining the TE performances, because the barrier energy can directly enhance Seebeck coefficient ( S ). We have succeeded in precisely tuning the barrier energy in poly (3, 4-ethylene dioxythiophene) polystyrene sulfonate (PEDOT:PSS)/Bi2 Te3 nanowires (NWs) based organic/inorganic nanocomposite films through polar solvent vapor annealing (PSVA). Controlling the PSS/PEDOT ratio as a function of PSVA duration, the work function of PEDOT:PSS was tuned, which eventually varied the barrier energy of nanocomposite thin films. Through optimization of Bi2 Te3 /PEDOT:PSS barrier energy, the S was maximized up to 47 μV/K. The electrical conductivity was also maximized simultaneously, because of the PSVA-induced π-π stacking among PEDOT chains and templating effect. Density functional theory calculated an optimal barrier energy (0.12 eV), which showed an excellent agreement with our experimentally determined optimal barrier energy (0.11 eV), at which we also maximized the power factor—an efficiency indicator of TE performance. Our feasible strategy on the manipulation of barrier energy in PEDOT:PSS/Bi2 Te3 NWs through the PSVA can be extended to other organic/inorganic based TE composites, toward the realization of highly efficient TE devices. Graphical abstract: Image 1 Highlights: We tuned the barrier energy of PEDOT:PSS/Bi2 Te3 nanowires through simply varying the PSVA duration. Simultaneous enhancement of Seebeck and electrical conductivity is achieved by optimizing the barrier energy. We achieved a power factor maximum of 223 μW/mK 2 when the barrier energy, Δ E =0.11 eV, at PSVA duration for 120 min. The optimized barrier energy for the enhanced Seebeck coefficient agrees well with the DFT calculated Δ E of 0.12 eV.